Impact of flood inundation after flood disaster in Tanah Merah, Kelantan - Jemali, Noor Janatun Maqwa (2016)
Over the past 30 years, floods have been the most tragic natural disaster affecting about 80 million people per year causing economic damage worth over USD11 million annually around the world. In December 2015, flooding in Kelantan has been classified as the worst in the history of the state. Conventional methods of assessing flood hazard are unable to provide quick, efficient and effective solutions. This study using ArcGIS to determine the differences of agriculture area of two consecutive dates that represent pre-flood and post-flood disaster. Images from Google Earth and agriculture map of Tanah Merah used as the raw data of this study. There were changes in area of agriculture landuse that shows that flood give impact for this type of area. Findings from this work will provide the necessary benchmark (especially in terms of agricultural land use) for a more comprehensive approach to manage the impact of flood disasters in the near future.